Implications of vitamin D levels or status for mortality in rheumatoid arthritis: analysis of 2001-2018 data from the National Health and Nutrition Examination Survey - Feng, Yalin; Zhu, Ping; Yan, Dandan; Wang, Xu; Chen, Caiyun; Zhang, Zhongyuan; Tian, Yian; Wang, Jiajia; Liu, Shanshan; Li, Ju; Meng, Deqian; Wang, Kai (Frontiers in Immunology, 2024)
Background: Inadequate levels of vitamin D (VitD) have been linked to increased rates of various health conditions and mortality. However, little is known about the relationship between mortality outcomes and 25-hydroxyvitamin D [25(OH)D] levels in individuals with rheumatoid arthritis (RA). This study aimed to examine this association using data from the National Health and Nutrition Examination Survey. Methods: A cohort of 2,290 individuals aged 20 to 85 years with RA was analyzed. Lower 25(OH)D levels were inversely associated with all-cause mortality, with a hazard ratio (HR) of 0.91 (0.87 to 0.96) per 10 nmol/L increase. Comparatively, the HR for the VitD insufficiency group was 0.64 (0.50 to 0.83), and for the VitD sufficiency group, it was 0.60 (0.44 to 0.80), both compared to the VitD deficiency group. Cause-specific analysis showed that higher 25(OH)D levels were associated with reduced mortality from heart disease (HR: 0.88, 0.82 to 0.95) and malignant neoplasms (HR: 0.86, 0.79 to 0.94). No significant correlation was found between 25(OH)D levels and cause-specific mortalities for other conditions. Results: Stratified by gender, the HR for males was 0.92 (0.85 to 0.99) and for females was 0.91 (0.86 to 0.98) per 10 nmol/L increase in 25(OH)D levels. Among individuals aged 20-59 years, no significant correlation was observed, while for those aged 60 years and older, the HR was 0.86 (0.82 to 0.90) per 10 nmol/L increase. Nonlinear analysis identified a sharp increase in HR below 59.95 nmol/L, while HR remained below 1 for 25(OH)D levels above 59.95 nmol/L. Conclusion: This study reveals a strong negative correlation between 25(OH)D levels and overall mortality in individuals with RA. Notably, this association is particularly significant for mortality related to heart disease and malignant neoplasms. Targeted VitD supplementation should be emphasized, especially in individuals aged 60 years and older with RA. The proposed minimum threshold for adequate 25(OH)D levels in the RA population is 60 nmol/L.